Primeros registros del Paiño de Elliot (Oceanites gracilis) en la Argentina - Pearman, Mark (2000)
Two specimens of Oceanites gracilis collected in El Bolsón, west Río Negro province, Argentina, in February 1972 and November 1983, represent the first records of the species in Argentina. These specimens, collected 950 km south of the known range, are suspected to originate accidentally from the Pacific Ocean in southern Chile, by influence of El Niño Southern Oscillation (ENSO) and 'classic' low pressure, combined with strong fronts, forcing the birds to cross low Andean passes.